she would have 4/8 left and that how much she will have
Answer:
Equation 3
Step-by-step explanation:
Lets see which of the functions has -2 as a zero root. We will go in order:
(1) (-2)^4 - 3(-2)^3 + 3(-2)^2 -3(-2) + 2 = 16 - 3(-8) + 3(4) + 6 +2 = 16 +24 +12 + 6 +2 =60 >0
So, (1) is wrong!
(2) (-2)^4 + 3(-2)^3 + 3(-2)^2 - 3(-2) - 2 = 16 - 24 + 12 + 6 - 2 =34 - 26 = 8 > 0
(2) is also wrong!
(3) (-2)^4 + 3(-2)^3 + 3(-2)^2 +3(-2) + 2 = 16 - 24 + 12 - 6 + 2 = 30 -30 = 0
The zero root x=-2 fits, what about x=-1?
(-1)^4 + 3(-1)^3 + 3(-1)^2 +3(-1) + 2 = 1 - 3 + 3 - 3 + 2 = 6 - 6 = 0
So, equation (3) fits both!
Finally, lets see (4):
(-2)^4 - 3(-2)^3 - 3(-2)^2 + 3(-2) + 2 = 16 + 24 - 12 - 6 + 2 = 42 - 18 = 24 > 0
So, (4) is also wrong.
Only equation 3 fits both zero roots!
The quartic function with x=-1 and x=-2 real roots is x^4+6x^3 +12x^2+12x+4. Quartic functions are polynomial functions of degree 4; quadratic equations resources also help understand the concept. In essence, finding roots of quartic functions follow the same logic as that of quadratic functions.
The subject matter pertains to quartic functions in mathematics. Quartic functions are polynomial functions with a degree of 4. From the question, the given zeros are x=-1 and x=-2, having multiplicity of 2 each (since there are only two real zeros). Thus, the quartic function with these zeros will be (x+1)^2*(x+2)^2. This can be expanded to x^4+6x^3 +12x^2+12x+4.
Exemplifying the relevance of The Solution of Quadratic Equations, normally known as second-order polynomials or quadratic functions, such equations can also be used to find zeros of the functions when set to equal zero. In this scenario, quartic functions are a degree higher, but the same principle applies in finding the roots when the equation is set equal to zero.
#SPJ3
-8x - 6y=-4
Answer:
x=5 y =-6
Step-by-step explanation:
- 8x-10y=20
-8x - 6y=-4
Multiply the first equation by -1
8x +10y=-20
Add this to the second equation
8x +10y=-20
-8x - 6y=-4
------------------
4y = -24
Divide each side by 4
4y/4 = -24/4
y = -6
Now we need to solve for x
8x +10(-6) = -20
8x -60 = -20
Add 60 to each side
8x -60+60 = -20+60
8x = 40
Divide each side by 8
8x/8 = 40/8
x =5
Answer:
his rate of miles per hour would be 7.5 mph
Sandra's statement is incorrect because she equated the expression (4 times 30) + (4 times 2) with the quotient of 128 divided by 4, which are two different values.
We have,
No, Sandra is notcorrect in her statement.
Let's break down the given expression and evaluate the quotient separately.
First, let's simplify the expression (4 times 30) + (4 times 2):
(4 x 30) + (4 x 2) = 120 + 8 = 128
Now, let's evaluate the quotient for 128 divided by 4:
128 divided by 4 = 32
So, the correctquotient for 128 divided by 4 is 32, not 8.
Thus,
Sandra's statement is incorrect because she equated the expression (4 times 30) + (4 times 2) with the quotient of 128 divided by 4, which are two different values.
Learn more about expressions here:
#SPJ6